COMPUTER MODELING OF MICROWAVE STRIPLINE RESONATORS FOR NON-INVASIVE SENSING - Minasyan, B.J.; Odabashyan, L.A.; Baghdasaryan, Zh.A.; Babajanyan, A.Zh.; Lee, K. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2019)
Microwave stripline resonators of rectangular and double rectangular shapes for non-invasive sensing have been designed and investigated experimentally and numerically. The resonator of single rectangular shape has had a resonance at about 4.32 GHz for $ S_{21} $ and the resonator of double rectangular shape has had resonances at about 3.5 GHz for $ S_{21} $ and 5.85 GHz for $ S_{11} $. The simulation results for the sensitivity of the single rectangular and double rectangular resonators were -0.023 dB/(mg/dL) (glucose concentration) and 0.0143 dB/(mg/dL) (NaCl concentration), respectively. The electromagnetic field distribution of the resonators was visualized and compared using computer simulation software HFSS. The obtained data have shown the accuracy of resonators as a non-invasive sensor for biophysical applications.
Keywords: microwaves stripline resonator; glucose sensing